Building the Nation's Character: A Study of 7 Habits of Indonesian Children in the Perspective of Civic Education - Hijran, Muhamad; Indrayati, Tri; Farid, Akbar (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Instilling character values through daily habits is an integral part of civic education, especially at the stage of child development. This study aims to examine the relationship between the seven habits of Indonesian children and the strengthening of civic education values through a literature study approach. The method used is a literature review of various scientific journals, research reports, and other relevant sources. The results of the study show that the seven habits have a close relationship with civic values, such as social care, active participation in community life, obedience to norms and laws, and respect for diversity. These findings affirm the importance of strengthening citizenship-based character education through the integration of positive habits in the family, school, and community environment. This study recommends that citizenship education be not only provided cognitively, but also through the internalization of national values that are manifested in children's daily behavior.